Targeting multi-loop integrals with neural networks - Winterhalder, Ramon; Magerya, Vitaly; Villa, Emilio; Jones, Stephen; Kerner, Matthias; Butter, Anja; Heinrich, Gudrun; Plehn, Tilman (SciPost physics, 2022)
Numerical evaluations of Feynman integrals often proceed via a deformation of the integration contour into the complex plane. While valid contours are easy to construct, the numerical precision for a multi-loop integral can depend critically on the chosen contour. We present methods to optimize this contour using a combination of optimized, global complex shifts and a normalizing flow. They can lead to a significant gain in precision.